2016
DOI: 10.1002/alr.21844
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli–derived and Staphylococcus aureus–derived extracellular vesicles induce MUC5AC expression via extracellular signal related kinase 1/2 and p38 mitogen‐activated protein kinase in human airway epithelial cells

Abstract: The results of this study suggest that E. coli-derived and S. aureus-derived EVs induced MUC5AC expression via ERK1/2 and p38 MAPK signaling pathways in human airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Consequently, our knowledge regarding Gram-positive EVs still remains limited (Brown et al, 2015 ). Since 2009, a few works reported the production and secretion of EVs by S. aureus , with particular emphasis on their protein content characterization and their impact on host cells (Lee et al, 2009 , 2013b ; Gurung et al, 2011 ; Hong et al, 2011 ; Kim et al, 2012 ; Thay et al, 2013 ; Choi et al, 2015 ; Jeon et al, 2016 ; Bae et al, 2017 ; He et al, 2017 ; Im et al, 2017 ; Jun et al, 2017 ; Askarian et al, 2018 ). In analogy with Gram-negative bacteria S. aureus EVs harbor, inter alia , numerous virulence factors, can have cytotoxic effects on host cells in vitro (Gurung et al, 2011 ; Jeon et al, 2016 ) and trigger a pro-inflammatory response both in vitro and in vivo (Hong et al, 2011 ; Kim et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, our knowledge regarding Gram-positive EVs still remains limited (Brown et al, 2015 ). Since 2009, a few works reported the production and secretion of EVs by S. aureus , with particular emphasis on their protein content characterization and their impact on host cells (Lee et al, 2009 , 2013b ; Gurung et al, 2011 ; Hong et al, 2011 ; Kim et al, 2012 ; Thay et al, 2013 ; Choi et al, 2015 ; Jeon et al, 2016 ; Bae et al, 2017 ; He et al, 2017 ; Im et al, 2017 ; Jun et al, 2017 ; Askarian et al, 2018 ). In analogy with Gram-negative bacteria S. aureus EVs harbor, inter alia , numerous virulence factors, can have cytotoxic effects on host cells in vitro (Gurung et al, 2011 ; Jeon et al, 2016 ) and trigger a pro-inflammatory response both in vitro and in vivo (Hong et al, 2011 ; Kim et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,13 Several inflammatory mediators induce MUC5AC expression in asthma, chronic obstructive pulmonary disease, and chronic bronchitis: inflammatory cytokines, hormones, chemicals, bacterial proteinases, and enzymes significantly induced MUC5AC expression in human airway epithelial cells. [14][15][16] For example, IL-1␤, a member of the IL-1 subfamily, is well known as a inflammatory mediator, which significantly induces MUC5AC expression in various cells, including NCI-H292 cells, hemoglobin subunit epsilon 1 transformed cells, and primary differentiated human nasal epithelial cells. 17 Several studies indicate that IL-36␥ is involved in the response of inflammation in the airway: lipopolysacchardie induces the production and release of IL-36r from monocytes in mouse lungs.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the signaling pathway of IL-36␥ and MUC5AC expression, two studies reported on activation of the IL-36 receptor and the phosphorylation of ERK1/2, p38, and NF-B: IL-36 activates the IL-36 receptor and induces mitogen-activated protein kinases and NF-kB in bronchial epithelial cells, 7,10 and several inflammatory mediators induce MUC5AC expression via ERK1/2, p38, and NF-B in human airway epithelial cells [14][15][16] ; therefore, this study focused on the IL-36 receptor, ERK1/2, p38, and NF-B in signaling pathway of IL-36␥-induced MUC5AC expression. The results of this study showed that IL-36␥ activated the phosphorylation of ERK1/2, p38, and NF-B.…”
Section: Figure 3 the Activation Of The Il-36 Receptor-mediated Erk1mentioning
confidence: 99%
“…The results were as described. 22 PCR products were quantified and normalized to glyceraldehyde-3phosphate dehydrogenase (GAPDH). Products were then detected using 2% agarose gel and visualized by staining with SYBR Safe DNA gel stain (Invitrogen, Carlsbad, CA) and transilluminated with an ultraviolet (UV) light source.…”
Section: Reverse-transcription Polymerase Chain Reaction Analysismentioning
confidence: 99%
“…The primer sequences and conditions used were according to published protocols. 22 Enzyme-linked immunosorbent assay…”
Section: Real-time Pcr Analysismentioning
confidence: 99%